Botswana : Technical Assistance Report-National Accounts Mission. (IMF Staff Country Reports; Country Report ;, 2020)
A technical assistance (TA) mission was conducted by IMF's Regional Technical Assistance Center for Southern Africa (AFS)1 during June 8-12, 2020 to assist Statistics Botswana (SB) in improving the quality of the national accounts statistics. The mission was conducted remotely respecting the constraints imposed by the COVID-19 outbreak. Reliable national accounts are essential for informed economic policymaking by the authorities. It also provides the private sector, foreign investors, rating agencies, donors and the public in general with important inputs in their decision-making, while informing economic analysis and IMF surveillance. Rebasing the national accounts is recommended every five years. Rebasing requires comprehensive surveys and ideally, supply and use tables (SUT) to support coherence checking of data.